JSON Implementation with Zlib Compression for Database Efficiency in Handling Dynamic Upload Multiple Images - Rianto Rianto; Alam Rahmatulloh; Iqbal Muhammad Fajar Nuralam (Journal of Telematics and Informatics, 2020)
In this era, in an application it is often found that a dynamic input form is a form that can be filled in a lot of data, the application user is free to fill the data according to his wishes. To handle this dynamic input form, the developer usually adds a new table in a database specifically for storing dynamic data, it has the potential to waste tables and records in a database. Applying the JSON conversion technique is a solution to overcome this, dynamic data is stored in a special field so that the use of tables and records can be minimized, as well as to compress the JSON string length applied by the Zlib algorithm. In this study, dynamic data is a images file uploaded on an input form. The results of this study in the case of handling multiple dynamic form upload images shows that the JSON conversion technique is better than conventional techniques in terms of faster data storage speeds of 72.6%, in terms of simpler database structures, and in terms of 22.7% more data size small, so database management becomes more efficient.